The Influence of Personal Selling and Sales Promotion on Consumer Purchasing Decisions at Jafar Plaza Bangunan Tukka Store, Central Tapanuli Regency - Wina Adhela Panggabean; Mansur Tanjung; Dicky Syahputra Lubis (Journal of Economics, Management and Accounting (JEMA), 2026)
Increasing competition in the building materials retail sector requires businesses to implement effective marketing strategies to enhance consumers' purchasing decisions. This study aims to analyze the effects of personal selling and sales promotion on consumer purchasing decisions at Jafar Plaza Bangunan Tukka Store, Central Tapanuli Regency, both partially and simultaneously. This study employed a quantitative approach with an associative research design. The sample consisted of 40 respondents selected using an accidental sampling technique. Data were collected through a Likert-scale questionnaire and analyzed using multiple linear regression with IBM SPSS Statistics version 27. The results showed that the regression equation was Y = 4.319 + 0.427X₁ + 0.447X₂. Partially, personal selling had a positive and significant effect on purchasing decisions (t = 2.679; p = 0.011), while sales promotion also had a positive and significant effect on purchasing decisions (t = 3.824; p < 0.001). Simultaneously, personal selling and sales promotion had a positive and significant effect on consumer purchasing decisions (F = 20.532; p < 0.001). These findings indicate that improving salespersons' interaction quality and implementing well-designed sales promotion programs can significantly increase consumer purchasing decisions at Jafar Plaza Bangunan Tukka Store, Central Tapanuli Regency.